Student’s Creative Thinking Process about Numeracy: A Case of Student’s Adversity Quotient (AQ) - Cahyati, Vania Idelia; Siswono, Tatag Yuli Eko; Wijayanti, Pradnyo (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2024)
The study aims to describe the creative thinking process of junior high school students with different Adversity Quotient (AQ) categories (quitter, camper, and climber) in solving numeracy problems. This qualitative research involves three subjects representing distinct AQ categories. Data collection includes the ARP questionnaire, numeracy problem-solving tests, and interviews, with analysis using the Pierce sign concept. Findings reveal camper and climber subjects effectively separate information in the ideation stage, while quitter and climber subjects associate knowledge concepts in generating idea. In preparing a plan for application, camper and climber subjects strategize based on information and knowledge, while in applying an idea, quitter subjects surrender, campers choose easier alternatives, and climbers persist with pre-planned strategies. Results suggest tailored motivation according to students' AQ categories can enhance teacher-student engagement.